STRENGTHENING AWARENESS OF MINING COMPANIES THROUGH SOCIALIZATION OF SUSTAINABILITY REPORTING AND CARBON TAX IN SOUTHEAST SULAWESI - Safaruddin, Safaruddin; Hadisantoso, Erwin; Anto, La Ode; Arifuddin, Arifuddin; Abdullah, Muntu; Asni, Nur; Purnaman, Si Made Ngurah; Nagu, Nadhirah; Putry, St. Syadiah; Putera, Asrip (Yayasan Education and Social Center, 2025)
Awareness of the importance of sustainability reporting and carbon taxes is a significant issue for mining companies in Southeast Sulawesi. While contributing greatly to the local economy, these companies face environmental and social challenges. Sustainability reporting demonstrates a commitment to social and environmental responsibility, while carbon taxes encourage emissions reductions and the adoption of green technologies. However, implementation remains constrained by low management understanding and limited infrastructure. Studies show that the readiness of companies in this area is still low in facing these regulations. Intensive socialization is needed to increase company awareness and readiness. Collaboration between the government, companies and communities is essential to overcome this challenge. The objective of socialization is to improve companies' understanding of sustainability reporting and carbon tax, strengthening transparency, accountability, and positive contributions to the environment and society. The benefits include the integration of sustainability principles in business, increased transparency, strengthened accountability, increased investor confidence, asset management efficiency, and the application of better accounting standards.